Creation of a Waste Bank to Improve the Discipline of the Karanganyar Village Community in Waste Sorting and Management - Primanda, Fairuz; Rahman, Ilham Aulia; Aisy, Egidia Rikhadatul; Wibawa, Rizki; Hanum, Naswa Allivia; Putra, Lutfiansyah Bayu Eka; Purwanto, Hafidz Edi; Purwaningsih, Atun; Widianingsih, Widianingsih; Firdaus, Rizky Nur Lalita; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to describe the process of establishing a waste bank in Karanganyar Village, Adipala Sub-district, Cilacap Regency, and to evaluate its role in improving community discipline in sorting and managing waste. The method used is Participatory Action Research (PAR), which emphasizes the active involvement of the community, students from the Community Service Program (KKN) of Muhammadiyah University of Purwokerto, and village officials at all stages of the activity. The approach is descriptive qualitative, with data collection through observation, interviews, documentation, and focus group discussions (FGD). The construction of the waste bank was carried out in stages, starting from planning, procurement of materials, construction using Hebel blocks with dimensions of 80 cm in height, 250 cm in length, and 120 cm in width, to the final completion consisting of two compartments for organic and inorganic waste. The research results indicate that the presence of the waste bank facilitates waste sorting at the household level, improves residents’ discipline in disposing of waste according to categories, and fosters collective awareness of the importance of maintaining environmental cleanliness. This program not only provides physical waste management facilities but also shapes positive and sustainable community behavior, thereby having the potential to serve as a model for community-based waste management that can be applied in other areas.